The influence of cognitive load and vision variability on postural balance in adolescents with intellectual disabilities - Jouira, Ghada; Alexe, Dan Iulian; Moraru, Cristina Elena; Rekik, Ghazi; Alexe, Cristina Ioana; Marinău, Marius Alin; Sahli, Sonia (Frontiers in Neurology, 2024)
This study aimed to investigate the impact of cognitive load, particularly its escalation during the execution of the same test, under varying vision conditions, on postural balance among adolescents with intellectual disability (ID). Twenty adolescents underwent balance assessments under different visual conditions (Open Eyes (OE), Closed Eyes (CE), Flash, Goggles, Visual Stimulation (VS)) and task settings (Single Task (ST), Dual Task (DT) without challenges, and DT with challenges). The cognitive test was assessed using Verbal Fluency (VF). Significant effects were found for Task (p<0.001, ηp²=0.85), indicating that CoP values significantly increased (p<0.05) with the introduction of the DT. Dual Task Cost (DTC) demonstrated significant effects for Vision (p=0.008, ηp²=0.62), with values varying significantly (p<0.05) among different vision conditions, especially in CE and Flash conditions. Visual Dependency Quotient (VDQ) analyses revealed significant effects of condition (p<0.001, ηp²=0.84), with significant changes observed in CE/OE and Flash/OE conditions (p<0.05). Significant effects were observed for Cognitive performance in the Challenge condition (p< 0.001, ηp²=0.86), with decreased performance with cognitive task challenges, particularly in Flash and Goggles conditions (p<0.05). In conclusion, cognitive tasks, especially challenging ones, and visual variations significantly impact postural balance in adolescents with ID.